2022
DOI: 10.3390/brainsci12070929
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Neuroplastic Changes after Transcranial Magnetic, Electric, and Deep Brain Stimulation

Abstract: Electric and magnetic stimulation of the human brain can be used to excite or inhibit neurons. Numerous methods have been designed over the years for this purpose with various advantages and disadvantages that are the topic of this review. Deep brain stimulation (DBS) is the most direct and focal application of electric impulses to brain tissue. Electrodes are placed in the brain in order to modulate neural activity and to correct parameters of pathological oscillation in brain circuits such as their amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 259 publications
(323 reference statements)
0
33
0
1
Order By: Relevance
“…MEP: motor evoked potential. Modified from [ 77 ]. MEP: motor evoked potential; rTMS: repetitive transcranial magnetic stimulation.…”
Section: Figurementioning
confidence: 99%
“…MEP: motor evoked potential. Modified from [ 77 ]. MEP: motor evoked potential; rTMS: repetitive transcranial magnetic stimulation.…”
Section: Figurementioning
confidence: 99%
“…Finally, Kricheldorff et al [ 9 ] present a narrative review on the possibilities of different brain stimulation techniques, i.e., magnetic, electrical, and deep brain stimulation, to modulate cortical neuroplasticity (i.e., MEP, EEG, magnetoencephalography outcomes) and clinical as well as behavioral outcomes. They elegantly tackle the mechanisms of action of these techniques and suggest future paradigms to pave the way for forthcoming research.…”
Section: Neurophysiology and Neurostimulationmentioning
confidence: 99%
“…6 In the last two decades, it has become an instrument to investigate the cortical neural plasticity mechanisms and motor learning, given its capacity for prolonged changes in brain excitability, even after the stimulation period has ended. 7 Moreover, recent studies have shown that associating tDCS with other therapies may favor longer-lasting effects than when the therapy is executed alone. 8 Thus, the hypothesis of the study is that the tDCS associated with TMAP can enhance and prolong the effects of training alone.…”
Section: Introductionmentioning
confidence: 99%